Naval policy and cruiser design, 1865-1890 - Rodger, N (1974)
Naval history,like military history, has until recently concerned itself largely with battles, or at least with wars. The implicit assumption was presumably that the key to history was to be found in these turning-points, rather than in the piping times of peace. A fighting service was only really of interest when fighting. In recent years this approach has been largely abandoned, and it is now recognized that warfare is an extension, not only of politics, but of most other activities of man; that it is in itself one of his most characteristic activities, and may be studied to reveal most of his characteristics. The present study falls into this pattern. In that it traces the progress of warship design, it may be taken as a traditional technical study. In that it covers the formation of grand strategy and naval policy it may be thought of as an essay in the moulding of government decisions. As a survey of the administrative development of the Admiralty, it falls into another possible category. Finally, in charting the rise of professional studies and the intellectual growth of the Victorian naval officer it touches directly on social history. It is the writer's belief that a fighting service, especially one with so distinct and independent a character as the Navy, may be studied as a society in itself, or as a microcosm of society in general. It was with these considerations in mind that the years 1865 to 1890 were chosen. Paradoxically enough from the viewpoint of the old approach to naval history,they were years of general peace; it is contended that they were not the less interesting for that,but rather the more. One may almost say that the absence of major naval battles or campaigns allowed naval development to proceed along a steady course,undisturbed by adventitious factors. The influences at work upon the Navy and its policy are the more easily discerned without the distractions of actual operational experience. It is this which lends peculiar interest to the period; in no other age of British history were naval officers more remote from the experience of naval war. Of the thirty or so officers who sat at the Board of Admiralty "between 1866 and 1890,none had ever fought in a naval battle of any importance. They had "been present at numerous "bombardments,they had led landing parties and boat actions,stormed cities and stockades, fought in river,swamp and jungle, against pirates, savages, and slavers; but they had no experience of naval warfare on the high seas. This gives a unique quality to the age; to borrow a metaphor from medicine, it was sterile, uncontaminated with reality. [Continued in text ...]